Genetic diversity of Lippia rotundifolia Cham. in Minas Gerais, Brazil - Meira, Messulan Rodrigues; Martins, Ernane Ronie; Resende, Luciane Vilela (Acta Scientiarum. Biological Sciences, 2019)
Lippia rotundifolia is an aromatic species, endemic from Campos rupestres and isolated by mountains. We aimed with the research to study the genetic variability of chá-de-pedestre (Lippia rotundifolia Cham.) with natural occurrence in ten places of the State of Minas Gerais, from molecular markers of ISSR type. The places of collection were: Parque Estadual de Serra Nova; Parque Estadual Veredas do Peruaçu; Abóboras community; Gigante community; edge of Rio do Peixe; environmental preservation area of Olhos d´água; private property in Joaquim Felício; Parque Estadual do Rio Preto; São Gonçalo do Rio das Pedras and brook of Rio Tigre. After the establishment of the extraction and amplification of DNA fragments with primers ISSR, an array of genetic distance was built. From this matrix, we analyzed the genetic diversity index as the allelic frequency (Na and Ne), Shannos´s index (H´), polymorphism (PLP), heterozygosity (He) and gene flow (Nm). The result showed higher genetic variability within the population (93%). The genetic diversity index was low (He = 0.132; H´= 0.214; Na = 1.111; Ne = 1.183; PLP = 56.67%). In general the species have low genetic diversity. The greatest diversity in populations occurred with an average temperature of 20°C. The Rio Tigre showed higher genetic distance and isolation.